Phytochemical and proximate analysis of wild plants from the Gaza Strip, Palestine - MOHAMAD MAHMOUD ABOU AUDA (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Abou Auda MM. 2025. Phytochemical and proximate analysis of wild plants from the Gaza Strip, Palestine. Biodiversitas 26: 1085-1094. This study focused on the proximate analysis and nutritional evaluation of some mineral elements in different parts of fifteen plants collected from various locations in the Gaza Strip, Palestine. The parameters analyzed include total carbohydrates, crude fiber, moisture content, ash content, total protein, and total lipids, as well as the nutritional value. The study found significant differences in the chemical composition among the plants. The highest calculated nutritive value was for the Polygonum equisetiforme stem (410.01 Kcal/100g), while the lowest was for the Silybum marianum leaf (286.75 Kcal/100g). The findings revealed that the investigated plants might serve as valuable sources of many significant macro-nutrients, such as N, P, and K. The N concentration was highest in the Sinapis arvensis leaf (2.6%) and lowest in the Polygonum equisetiforme stem (0.44%). The P concentration was highest in Centaurea iberica leaf (0.3%) and lowest in P. equisetiforme leaf (0.18%). The K concentration was highest in the S. arvensis flower (4.33%) and lowest in the P. equisetiforme stem (1.4%). The findings revealed that these plants could serve as nutritional supplements and therapeutic aids as they are rich in essential nutrients, including proteins, carbohydrates, lipids, and fibers. Additionally, their significant mineral contents that make them beneficial for addressing malnutrition and supporting livestock growth.